Penerapan Metode Scaffolding Pada Zone Of Proximal Development (ZPD) Dalam Meningkatkan Hasil Belajar Siswa Kelas X-1 SMAN 6 Kota Tangerang Selatan - Marlina, Lina; Rahayu, Yayuk Muji (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
The objective of this research is to improve the learning outcomes of students in Class X-1 at SMAN 6 Kota Tangerang Selatan through the application of the scaffolding method within the Zone of Proximal Development (ZPD). The scaffolding method in the Zone of Proximal Development (ZPD) is a concept of student development proposed by Vygotsky, as noted in Ratnawati Mamin's journal. Vygotsky's concept encompasses two primary aspects of student ability development: actual and potential development abilities (Mamin, 2008, p. 56). These two concepts rely on students' ability to work independently with guidance and direction from adults. Applying the scaffolding method within the ZPD helps students overcome learning difficulties, strengthens their understanding, and significantly enhances their learning outcomes. Students can also gradually progress with appropriate support from teachers, peers, and other resources. The subjects of this research are the teachers and students of Class X-1 at SMAN 6 Kota Tangerang Selatan. This study uses a qualitative approach combined with a quantitative approach through a classroom action research method, as the main objective of classroom action research is to improve and enhance educators' professional services in managing the teaching and learning process. The expected outcome is that the application of the Scaffolding Method within the Zone of Proximal Development (ZPD) can improve the learning outcomes of Class X-1 students at SMAN 6 Kota Tangerang Selatan.